Assessment of The Rakihan Lake Geosite Using Participatory Action Research and The Modified Geosite Assessment Model - Budhi Setiawan; Friska Adelia (Jurnal Ilmiah Dinamika Rekayasa, 2026)
This study presents a comprehensive assessment of the Rakihan Lake geosite in South OKU, Indonesia, utilizing Participatory Action Research (PAR) and the Modified Geosite Assessment Model (M-GAM). The PAR approach actively engaged local communities, government officials, and site managers throughout the research process, fostering collaboration and integrating local knowledge with scientific expertise. The M-GAM method was employed to evaluate the geosite’s main and additional values across 27 sub-indicators, reflecting both expert and visitor perspectives. Results indicate that Rakihan Lake possesses moderate principal value and low additional value, primarily due to limited geological knowledge, inadequate infrastructure, and restricted accessibility. Despite these challenges, the integration of PAR and M-GAM proved effective in identifying key areas for improvement and promoting participatory conservation strategies. The findings underscore the importance of community involvement and targeted geoeducation in enhancing the sustainability and development potential of geosites.